A new grape hyacinth from East Anatolia (Turkey) Muscari vanensis (subgenus Botryanthus) - Uysal, Tuna; Aksoy, Ahmet; Bozkurt, Meryem; Ertuğrul Kuddi̇si̇ (Phytotaxa, 2022)
Muscari vanensis (Asparagaceae) is described and illustrated from East Anatolia, Turkey. This species is distributed in slopes of stony rocky areas facing south of Lake Van (B5 Van Province). Muscari vanensis an endemic confined to East Anatolia, is related to mainly with M. botryoides and M. armeniacum. Diagnostic morphological characters have been discussed and compared with those of closely related taxa. At the first glance, the new species is easily separated from its relatives in its dwarf appearance and patent leaves, shorter scape, densely globose-oblong raceme, globose urceolate and swollen fertile flowers. Additionally, karyological, molecular and palynological data were used to support this diagnostic characters and to strengthen the taxonomic background of the new species.